Awareness on Breast Cancer among Women of Kedah State, Malaysia: A Cross-Sectional Study - Theingi Maung M; Christina Gellknight; Andrina Lourdes L; Siva Shangari J; Manpreet Kaur J S; Navdeep Kaur R S (Asian Journal of Medicine & Health Sciences, 2021)
Background: Breast cancer is one of the commonest cancers in all ethnic groups and in all age groups in females from the age of 15 years onwards. It is important to create adequate awareness regarding breast cancer in women in order to encourage more women to present to healthcare professionals at the onset of early symptoms. The objective of this study is to assess the awareness of breast cancer among the women of Kedah state, Malaysia. Methods: Cross sectional study was conducted among 100 females from Alor Setar, Kedah State. Participants were recruited by convenience sampling. Each participant was given a set of questionnaire and data analysis was done by the SPSS software. Results: In this study, 85% of the respondents knew that breast self- examination (BSE) was a useful tool for the early detection of breast cancer but one third of the participants did not practice it. Results showed that 54% of the respondents aware the right timing for breast self-examination but 15% thought it should be done by a healthcare professional. In this study, 50% of the respondents correctly answered that mammography should be started from age of 40. Conclusion: Overall awareness on breast cancer among the respondents was satisfactory. More intervention should be done to raise the level of awareness in women to reduce the rate of breast cancer morbidity and mortality.